2020
DOI: 10.25206/1813-8225-2020-173-103-110
|View full text |Cite
|
Sign up to set email alerts
|

Features of circuitry of acousto-optic laser measuring systems for controlling three-coordinate (3D) movements of products and equipment elements. Part 1

Abstract: The article is devoted to the construction of acousto-optic (AO) laser measuring systems (LMS) for measuring product displacements in three coordinates (3D): with one longitudinal Δl z and two transverse Δl x , Δl y with high resolution and an increased measurement range for the latter two. The paper discusses the circuitry of the measuring circuit based on the phase-locked loop (PLL) system, which makes it possible to achieve the maximum resolution when the AO LMS operates in the start-stop mode, i.e. starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At Δf=4·10 7 Hz and P NEP =30·10 -12 W/Hz 1/2 by using equation ( 12), the value Q≈1000 was calculated by calculation [15,16]. However, similar some articles [15,16,18,19], to increase the reliability of the results obtained, a lower value, namely, Q≈600, will be taken as the basis for further calculations. The calculations given in [15,16] showed that the level of shot noise was ~30% of the total noise level.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At Δf=4·10 7 Hz and P NEP =30·10 -12 W/Hz 1/2 by using equation ( 12), the value Q≈1000 was calculated by calculation [15,16]. However, similar some articles [15,16,18,19], to increase the reliability of the results obtained, a lower value, namely, Q≈600, will be taken as the basis for further calculations. The calculations given in [15,16] showed that the level of shot noise was ~30% of the total noise level.…”
Section: Resultsmentioning
confidence: 99%
“…It shows: laser 1, AO modulator 2, optical circuit 3, movable trippel prism 4, two microlenses 5 and 6 for two Y-shaped fiber-optic (FO) splitters 7 and 8, HF photodetector 9, LF photodetector 10, phase interpolator (in futureinterpolator) 11, PLL 12, adder 13, phase meter 14. The PLL 12 is described in [18][19][20] and has a standard circuit in the form of a ring from a serial circuit of a phase detector (with an additional digital output N pd ), a low-pass filter, a voltage-controlled generator (VCG) based on a highly stable quartz oscillator, the frequency output signal of which is fed to the AO modulator 2. The cutoff frequency of the low-pass filter is controlled by a frequency detector depending on the Doppler frequency rise, the effect of which is discussed further (not shown in figure 1).…”
Section: Structure and Principle Of Operation Of Linden Trees With Tw...mentioning
confidence: 99%
See 3 more Smart Citations